Chemical characteristics of compost and humic acid from sago waste (Metroxylon sagu) - Petrus Rudut, Auldry Chaddy; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad; Hassan, Mohammad Nasir; Jiwan, Make; Banta, Michael Gregory (Science Publications, 2009)
Problem statement: Agriculture waste such as Sago Waste (SW) has a potential to cause pollution either on land or in water. In order to reduce this problem, a study was conducted to investigate the effect of three different treatments on the chemical characteristics of compost and humic acid from SW. Approach: The study had three treatments which were: T1: SW (80%) + chicken feed (5%) + chicken dung slurry (5%) + molasses (5%) + urea (5%), T2: SW (80%) + chicken feed (10%) + chicken dung slurry (5%) + molasses (5%) and T3: SW (80%) + chicken feed (10%) + chicken dung slurry (5%) + urea (5%). Composting was done for 60 days in a white polystyrene box with a size of 61.5×49×33.5 cm. The composts were analyzed for pH, total nitrogen, organic carbon, organic matter, ash, Cation Exchange Capacity (CEC), phosphorus and HA using standard procedures. Results: All treatments did not reach thermophilic phase. Compost of T2 had high quality (pH, total nitrogen, organic carbon, organic matter, ash, Cation Exchange Capacity (CEC), phosphorus and HA) compared to T1 and T3. The yield of HA of T2 was also significantly higher compared to those of T1 and T3. The compost characteristics of T1 and T3 were similar. The chemical characteristics of HA the 3 treatments were within the standard range reported by other researchers. Conclusion: T2 is more efficient in producing mature and good quality compost in 60 days compared to T1 and T3.